Src Family Kinases Play a Role in the Functional Clustering of Central Postsynaptic Nicotinic Acetylcholine Receptors - Flynn, Nichole; Syed, Naweed I. (Frontiers in Marine Science, 2020)
The mechanism of postsynaptic neurotransmitter receptor clustering has been best described at the neuromuscular junction (NMJ), where pockets of nicotinic acetylcholine receptors (nAChRs) in muscle fiber are redistributed to the synaptic site upon motor neuron innervation. This process of receptor localization is facilitated by agrin signaling, and the stability of the resulting nAChR clusters depends upon the activation of Src family kinases (SFKs). In contrast to the NMJ, however, the cellular signaling mechanisms orchestrating the clustering of nAChRs in the central nervous system (CNS) remain poorly defined. Furthermore, our understanding of the role of SFKs in the CNS is also limited. Here, we provide evidence that SFK activation is required for synapse formation between pairs of identified neurons isolated from the CNS of Lymnaea stagnalis. Furthermore, we suggest that SFKs are involved in the functional redistribution of nAChRs to the synaptic contact sites in isolated axons. To the best of our knowledge, this study is the first to demonstrate a role for SFKs in the clustering of nAChRs in central neurons, suggesting that the mechanisms of receptor clustering between the peripheral nervous system (PNS) and CNS are likely conserved.